Efficacy and safety of electroacupuncture for carpal tunnel syndrome (CTS): A systematic review and meta-analysis of randomized controlled trials - Li, Ting; Yan, Jingxin; Hu, Jiang; Liu, Xilin; Wang, Fei (Frontiers in Surgery, 2022)
Aim: We carried out a systematic review and meta-analysis to evaluate the safety and efficacy of electroacupuncture for patients with carpal tunnel syndrome (CTS). Methods: We searched PubMed, Embase, Cochrane library, Scopus, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP Database (VIP) and Wan Fang Database up to May 2022 for relevant studies. Relevant studies were identified by using specific eligibility criteria and data was extracted. Results: A total of 26 randomized controlled trials with 1698 patients were included. Compared with routine treatment, electroacupuncture treatment had lower VAS (Visual Analog Scale) score (MD= -0.79, 95%Cl: -1.11 ~ -0.47, P<0.00001), and the symptom severity scale and function status scale in electroacupuncture group were significantly lower than control group (P=0.0001 and P=0.006). What’s more, the electrophysiological parameters in electroacupuncture group were better than control group. Electroacupuncture group had higher total effective rate than control group (OR=4.94, 95%Cl: 3.44~7.08, P<0.00001). Conclusion: Current evidence indicated that electroacupuncture had lower VAS score, higher total effective rate, a lower the scores of symptoms and function and electroacupuncture had better electrophysiological parameters. However, these findings needed to be verified in further by multi-center, double-blind and large sample RCTs.